MircroRNA Let-7a-5p in Airway Smooth Muscle Cells is Most Responsive to High Stretch in Association With Cell Mechanics Modulation - Wen, Kang; Ni, Kai; Guo, Jia; Bu, Bing; Liu, Lei; Pan, Yan; Li, Jingjing; Luo, Mingzhi; Deng, Linhong (Frontiers in Physiology, 2022)
Objective: High stretch (strain >10%) can alter the biomechanical behaviors of airway smooth muscle cells which may play important roles in diverse lung diseases such as asthma and ventilator-induced lung injury. However, the underlying modulation mechanisms for high stretch-induced mechanobiological responses in ASMCs are not fully understood. Here, we hypothesize that ASMCs respond to high stretch with increased expression of specific microRNAs (miRNAs) that may in turn modulate the biomechanical behaviors of the cells. Thus, this study aimed to identify the miRNA in cultured ASMCs that is most responsive to high stretch, and subsequently investigate in these cells whether the miRNA expression level is associated with the modulation of cell biomechanics. Methods: MiRNAs related to inflammatory airway diseases were obtained via bioinformatics data mining, and then tested with cultured ASMCs for their expression variations in response to a cyclic high stretch (13% strain) simulating in vivo ventilator-imposed strain on airways. Subsequently, we transfected cultured ASMCs with mimics and inhibitors of the miRNA that is most responsive to the high stretch, followed by evaluation of the cells in terms of morphology, stiffness, traction force, and mRNA expression of cytoskeleton/focal adhesion-related molecules. Results: 29 miRNAs were identified to be related to inflammatory airway diseases, among which let-7a-5p was the most responsive to high stretch. Transfection of cultured human ASMCs with let-7a-5p mimics or inhibitors led to an increase or decrease in aspect ratio, stiffness, traction force, migration, stress fiber distribution, mRNA expression of α-smooth muscle actin (SMA), myosin light chain kinase, some subfamily members of integrin and talin. Direct binding between let-7a-5p and ItgαV was also verified in classical model cell line by using dual-luciferase assays. Conclusion: We demonstrated that high stretch indeed enhanced the expression of let-7a-5p in ASMCs, which in turn led to changes in the cells’ morphology and biomechanical behaviors together with modulation of molecules associated with cytoskeletal structure and focal adhesion. These findings suggest that let-7a-5p regulation is an alternative mechanism for high stretch-induced effect on mechanobiology of ASMCs, which may contribute to understanding the pathogenesis of high stretch-related lung diseases.